2004
DOI: 10.1159/000079735
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Young Patients: Etiopathogenesis and Risk Factors in Different Age Classes

Abstract: The aim of our study was to evaluate the etiopathogenesis and the vascular risk factors in a consecutive series of patients with juvenile ischemic stroke. We enrolled 273 patients (158 males and 115 females), aged between 16 and 49 years, with ischemic cerebrovascular events (ICVE), including transient ischemic attack (TIA) or stroke, referred to our neurology ward between January 1994 and December 2001. Our protocol included medical history, cardiac and neurological examinations, assessment of risk factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
69
2
15

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 26 publications
19
69
2
15
Order By: Relevance
“…This corresponds to that of other stroke populations 18, 22. However, while some studies have observed higher proportions of large‐artery atherosclerosis earlier in life 23, 24, our population shows that large‐artery atherosclerosis appears in the 3rd decade, but was not a common finding before the 5th decade and thereafter increased until the 8th decade before decreasing again.…”
Section: Discussionsupporting
confidence: 84%
“…This corresponds to that of other stroke populations 18, 22. However, while some studies have observed higher proportions of large‐artery atherosclerosis earlier in life 23, 24, our population shows that large‐artery atherosclerosis appears in the 3rd decade, but was not a common finding before the 5th decade and thereafter increased until the 8th decade before decreasing again.…”
Section: Discussionsupporting
confidence: 84%
“…1,2 Embolism of cardiac origin is another main cause of TIA and ischaemic stroke in young patients. It has been estimated that 15 to 30% of all TIAs and ischaemic strokes are due to a cardioembolic source (CES).…”
mentioning
confidence: 99%
“…She was transferred urgently to our institution, where bedside trans-thoracic echocardiography revealed apical and anterior left ventricular Joanna Grogono, 1 ST3 cardiology; Samantha J Fitzsimmons, 2 specialist registrar in adult congenital heart disease; Benoy N Shah, 3 clinical research fellow; Dhrubo J Rakhit, 2 consultant cardiologist; Huon H Gray, 2 consultant cardiologist (LV) wall akinesis and overall moderate systolic dysfunction; subsequent cardiac biomarkers were markedly raised (troponin I 71 ug/L and creatine kinase 2049 iu/L). Serum cholesterol was normal (4.0 mmol/L).…”
Section: Lessonmentioning
confidence: 99%
“…A duplex ultrasound scan showed no evidence of deep venous thrombosis in the legs or pelvis, and blood screening for inherited and sporadic thrombophilia, vasculitis and antiphospholipid lesson of the month (2) Simultaneous myocardial infarction and ischaemic stroke secondary to paradoxical emboli through a patent foramen ovale Myocardial infarction (MI) and stroke are common acute conditions that regularly present as an emergency to hospital. Paradoxical embolism is a recognised complication of patent foramen ovale (PFO), and the literature shows that it can cause ischaemic stroke or, less frequently, acute MI.…”
Section: Lessonmentioning
confidence: 99%